Evaluation of Pulmonary Function Parameters in Children with Type 1 Diabetes Mellitus - Varma, Kosuri Mahesh; Sajjan, Shruti; Kulkarni, Keertivardhan; Patil, M.M. (International Journal of Child Health and Nutrition, 2025)
Background: Type 1 Diabetes Mellitus (T1DM) is a chronic autoimmune condition characterized by insulin deficiency. Emerging evidence suggests that type 1 diabetes mellitus (T1DM) may contribute to pulmonary dysfunction in children. Objectives: To evaluate pulmonary function changes in children with T1DM and assess the relationship of pulmonary function test (PFT) changes with glycemic control. Methods: A total of 62 children aged 6–16 years were enrolled, including 32 with type 1 diabetes mellitus (T1DM) and 30 healthy, age-matched controls. Spirometry parameters (FVC, FEV1, FEV1/FVC, PEFR) and diffusion capacity (DLCO) were assessed. Diabetic children were subgrouped based on glycemic control (HbA1c < 9.5 vs. > 9.5). Results: Children with T1DM had significantly lower FVC (p < 0.001), FEV1/FVC (p < 0.005), and DLCO (p < 0.03) compared to the control group. FEV1 and PEFR differences were not statistically significant. Among diabetic children, FEV1/FVC was significantly reduced in those with an HbA1c level greater than 9.5 (p = 0.003). Conclusion: Children with T1DM demonstrate early pulmonary impairment, especially restrictive changes with mixed ventilatory defects and decreased diffusion capacity. Routine spirometric screening may aid early detection of respiratory complications in pediatric diabetes.